Arterial lines: why, when, how?. (2nd March 2019) - Summerfield, Natasha
Abstract : Arterial lines are a useful tool in the emergency and intensive care patient. Invasive blood pressure measurement is considered the gold standard in patient care and has become commonplace in veterinary practice, especially in veterinary anaesthesia. Arterial catheters are catheters placed within the arterial lumen by a skilled veterinary surgeon or veterinary nurse. This catheter is attached to a monitor which provides information such as systolic, mean and diastolic arterial pressure, heart rate and an arterial waveform. Having an invasive arterial catheter gives the advantage of a constant measurement of arterial blood pressure, meaning the effects on patients of drugs, fluids and environment can be seen. Arterial lines are useful in patients where rapid changes in blood pressure are anticipated, and abnormal measurements can be detected quickly. This article discusses the different aspects of arterial lines from what they are, to waveform analysis and complications.